Validity evidence for the situational judgment test paradigm in emotional intelligence measurement - LIBBRECHT, Nele (Institutional Knowledge at Singapore Management University, 2012)
To date, various measurement approaches have been proposed to assess emotional intelligence (EI). Recently, two new EI tests have been developed based on the situational judgment test (SJT) paradigm: the Situational Test of Emotional Understanding (STEU) and the Situational Test of Emotion Management (STEM). Initial attempts have been made to examine the construct-related validity of these new tests; we extend these findings by placing the tests in a broad nomological network. To this end, 850 undergraduate students completed a personality inventory, a cognitive ability test, a self-report EI test, a performance-based EI measure, the STEU, and the STEM. The SJT-based EI tests were not strongly correlated with personality and fluid cognitive ability. Regarding their relation with existing EI measures, the tests did not capture the same construct as self-report EI measures, but corresponded rather to performance-based EI measures. Overall, these results lend support for the SJT paradigm for measuring EI as an ability.